ANALISIS PELAKSANAAN PENANGANAN KELUHAN PELANGGAN DAN PELAYANAN INFORMASI DI BPJS KESEHATAN KANTOR CABANG SEMARANG - Diah Eka Novitasari; Septo Pawelas Arso; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
BPJS Kesehatan has a target in 2019 that is to cover all indonesians, there are some problems with increasing health services, one of them is an increase in complaints in BPJS Kesehatan branch office Semarang. The objective of this study is to analyze the implementation of customer complaints handling and information services in BPJS Kesehatan branch office Semarang. The type of research is qualitative research with descriptive approach through observational method and a survey was conducted for participants as an output amplifier for the implementation of customer complaint handling. Key informants included front liner staff, participant complaint handling staff, front liner supervisors and triangulation informants including Head of KPP, Head of USDMKP, 5 Participants, and research respondents totaling 85 participants. The results showed on certain days participant complaint handling staff serving the participants exceed the workload (1:30), training from the center only followed by jobholders, counters 11 and 12 are still in the grievance room while laying service counters had to be parallel to other counters, promoting mobile JKN still not optimal, participant complaint handling staff sometimes forget to ask participants to fill out of CSTI (Customer Satisfaction Index). Output of the implementation of customer complaints handling in BPJS Kesehatan branch office Semarang has been objective, responsive, coordinative, effective and efficient, accountable and transparent in accordance with the results of a survey conducted to participants. The suggestion is adding participant complaint handling staff in the office for certain days, optimization of Mobile JKN Ambassador, making warning alarm set during customer complaints handling services and posting information at the door of the complaint room regarding the obligation to bring supporting evidence to participants.